Surfing the New Wave: Shakespeare with an Australian accent. Issue 1 (2nd January 2018) - Perry, Amy
ABSTRACT: This paper examines the evolution of Australian approaches to the production of Shakespeare's plays during and following the New Wave period. Theatre is a barometer and instigator of social change. By mapping Australia's evolving sense of national identity and its changing relationship with its colonial masters against changes on the stage, we can gain insight into Australia's evolving cultural relationship with Shakespeare. Tracing the trend from reverence to irreverence to ownership, this paper supplies a background to this evolution that continues to play out on the stage in contemporary Australian productions of Shakespeare.